Abu Dhabi International Petroleum Exhibition and Conference 2014
DOI: 10.2118/172023-ms
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Learning from Developing Deep High Pressure Sour Reservoirs in Southern Oman by EOR MGI

Abstract: The Sour Cluster is located in the south of the Sultanate of Oman. Since the first oil discovery in 1997, a successful exploration drilling campaign was carried out in the Cluster, resulting in the discovery of several carbonate stringer oil and gas reservoirs. Approximately half the gas volumes are contained in a gas condensate field. This field will be developed along with the other oil reservoirs in the cluster and will export gas to market as well as provide a source of make-up gas for the miscible gas inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It is believed that with the implementation of MGI, an estimated 47% of the original oil in place (OIIP) could be recovered . In fact, the MGI process is already being implemented in which the field’s AG mixture is the main gas source . The injection process has been carried out by reinjecting the AG mixture into the reservoir at high pressures (up to 55 MPa), and due to the high reservoir temperatures (up to 377 K), the gas becomes miscible with the oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that with the implementation of MGI, an estimated 47% of the original oil in place (OIIP) could be recovered . In fact, the MGI process is already being implemented in which the field’s AG mixture is the main gas source . The injection process has been carried out by reinjecting the AG mixture into the reservoir at high pressures (up to 55 MPa), and due to the high reservoir temperatures (up to 377 K), the gas becomes miscible with the oil.…”
Section: Introductionmentioning
confidence: 99%
“…7 In fact, the MGI process is already being implemented in which the field's AG mixture is the main gas source. 8 The injection process has been carried out by reinjecting the AG mixture into the reservoir at high pressures (up to 55 MPa), and due to the high reservoir temperatures (up to 377 K), the gas becomes miscible with the oil. However, even though the oil in Field A is light (42°API), the significant viscosity contrast between the injected gas (0.1−0.03) and oil (0.23 cP) leads to viscous fingering, early breakthrough, and high gas-to-oil ratio, which would compromise the macroscopic sweep efficiency of the field.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The field has a harsh reservoir environment with a formation brine salinity of 275,000 ppm TDS (total dissolved solids) and a reservoir temperature of 377 K with low in situ water saturation. 18,19 It has been shown that both foam and WAG flooding are not applicable in this field as means of mobility control. 16 Hence, with Field A, it is believed that AG mixture thickening may be the only viable approach to counteract unfavorable mobility conditions and improve sweep efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike foam injection and water alternating gas (WAG) flooding, the application of gas thickeners is not dependent on the reservoir rock petrophysical properties and fluid saturations . Field A in southern Oman has suffered from early gas breakthrough due to the high mobility of the AG mixture injected as part of an MGI process. , The field has a harsh reservoir environment with a formation brine salinity of 275,000 ppm TDS (total dissolved solids) and a reservoir temperature of 377 K with low in situ water saturation. , It has been shown that both foam and WAG flooding are not applicable in this field as means of mobility control . Hence, with Field A, it is believed that AG mixture thickening may be the only viable approach to counteract unfavorable mobility conditions and improve sweep efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the Middle East, many MGI projects are currently being undertaken in carbonate reservoirs in which the injected AG often contains acid gases. Field A, located in the Harweel cluster in southern Oman, has been recognized as a viable MGI candidate. The MGI in this field has already commenced where the source of the injection gas is the field’s AG . The AG mixture is reinjected into the reservoir at high pressure (up to 55 MPa) where it becomes miscible with the oil during the displacement at the relatively high reservoir temperature of up to 377 K. The AG in Field A contains CH 4 enriched with light and heavy hydrocarbon fractions found in natural gas and a significant amount of carbon dioxide at 10–25 mol% .…”
Section: Introductionmentioning
confidence: 99%